The book as an object of the shared understanding of media changes - Aunin, Tiina (Primerjalna književnost, 2012)
This essay advances a general cultural understanding of the book. It examines, compares, and evaluates the main approaches to the book in social and cultural theory as well as in everyday practice in all its richness. The hypothesis is that the book as a cultural object plays a crucial role in the sociodynamic activity of understanding the self in social performance.
Keywords: književnost; literature; družba; society; bralna kultura; mediji; communication medium; tehnološki razvoj; e-knjige; bralniki; kulturni prenos